Making use of mortality data to improve quality and safety in general practice: a review of current approaches. Issue 2 (2nd April 2007) - Baker, Richard; Sullivan, Emma; Camosso-Stefinovic, Janette; Rashid, Aly; Farooqi, Azhar; Blackledge, Hanna; Allen, Justin
Abstract : Objective: To review studies of the use of mortality data in quality and safety improvement in general practice. Design: Narrative review. Methods: Search of Medline, Embase and CINAHL for articles reporting mortality monitoring or mortality reviews in general practice. The included articles were reported in English and of any study design, excluding case reports and comment pieces. Studies of palliative care and bereavement, and of primary care programmes in developing countries, were excluded. Results: 229 articles were identified in the searches, 65 were identified as potentially relevant and 53 were included in the review. The studies addressed the impact of primary care provision on mortality rates, methods of monitoring mortality, and the role of audit and death registers in quality and safety improvement. General practitioners were interested in using mortality data but reported difficulties in obtaining complete information. There were no experimental studies of the impact of the use of mortality data, and little evidence of long-term systematic initiatives to use mortality data in quality and safety improvement in general practice. Conclusions: Mortality data are not used systematically in general practice although general practitioners appear interested in the potential of this information in improving quality and safety. Improved systems to provide complete data are needed and experimental studies required to determine the effectiveness of use of the data to improve general practice care.